Foreword - Pontes, José Antonio Siqueira; Kashiura Jr., Celso Naoto; Sanches Jr., Antonio Roberto (DESC - Direito, Economia e Sociedade Contemporânea, 2018)
Foreword to the first issue of the magazine DESC - Law, Economy and Contemporary Society.